2022
DOI: 10.1159/000524098
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Efficacy, and Safety of Sequential Intravesical Gemcitabine + Docetaxel versus BCG for Non-Muscle Invasive Urinary Bladder Cancer: A Pilot Study

Abstract: <b><i>Purpose:</i></b> Bacille Calmette-Guerin (BCG) is considered the most effective agent for non-muscle invasive bladder cancer (NMIBC). However, due to BCG-related toxicity, multiple studies have suggested the role of newer chemotherapeutic drugs. The aim of our study was to evaluate intravesical gemcitabine + docetaxel (Gem/Doce) versus BCG with respect to quality of life (QOL), safety, and efficacy in NMIBC. <b><i>Methods:</i></b> A total of 60 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Many similar AEs are a concern for gemcitabine and docetaxel therapy, but our results revealed that treatment discontinuation rates were lower for this chemotherapy doublet than for BCG. These findings are consistent with those of Pareek et al, who found in a prospective cohort of 60 patients that gemcitabine and docetaxel therapy was associated with better quality of life outcomes and fewer toxic effects when compared with BCG therapy. While overall tolerability was similar, patients in the present cohort who received gemcitabine and docetaxel were more likely to experience bladder spasms and nausea, while those who received BCG were more likely to experience distinct immunologic AEs, such as arthralgias and fatigue or flulike symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Many similar AEs are a concern for gemcitabine and docetaxel therapy, but our results revealed that treatment discontinuation rates were lower for this chemotherapy doublet than for BCG. These findings are consistent with those of Pareek et al, who found in a prospective cohort of 60 patients that gemcitabine and docetaxel therapy was associated with better quality of life outcomes and fewer toxic effects when compared with BCG therapy. While overall tolerability was similar, patients in the present cohort who received gemcitabine and docetaxel were more likely to experience bladder spasms and nausea, while those who received BCG were more likely to experience distinct immunologic AEs, such as arthralgias and fatigue or flulike symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…MeElree et al published a large study of 312 patients, of which almost 44% had CIS (alone or in combination) and almost one-third of them had a Ta cancer with HG RFS in 71% of patients with BCG treatment and 85% of patients with Gem/Doce [32], which is actually the same as we found in our study confirming the efficacy of this therapy especially in older patients who may be increasingly immunosenescent and therefore less suitable for BCG treatment. These authors also demonstrated that patients were less likely to quit Gem/Doce treatment because they had better quality of life and less toxic effects compared to BCG [32], confirming the findings reported from other studies [35]. In our study, only one patient reported probably unrelated complication which postponed treatment, thus verifying the safety and tolerability of this treatment.…”
Section: Discussionsupporting
confidence: 91%
“…MeElree et al published a large study on 312 patients, of which almost 44% had CIS (alone or in combination) and almost a third had a Ta cancer, with HG RFS in 71% of the patients with BCG treatment and 85% of the patients with Gem/Doce [34], which is actually the same result as we found in our study, confirming the efficacy of this therapy especially in older patients who may be increasingly immunosenescent and, therefore, less suitable for BCG treatment. These authors also demonstrated that patients were less likely to quit Gem/Doce treatment because they had a better quality of life and experienced fewer toxic effects compared to BCG [34], confirming the findings reported by other studies [37]. In our study, only one patient reported a-probably unrelated-complication that postponed treatment, thus verifying the safety and tolerability of this treatment.…”
Section: Discussionsupporting
confidence: 91%